2012
DOI: 10.5194/angeo-30-867-2012
|View full text |Cite
|
Sign up to set email alerts
|

More about arc-polarized structures in the solar wind

Abstract: Abstract.We report results from a Cluster-based study of the properties of 28 arc-polarized magnetic structures (also called rotational discontinuities) in the solar wind. These Alfvénic events were selected from the database created and analyzed by Knetter (2005) by use of criteria chosen to eliminate ambiguous cases. His studies showed that standard, four-spacecraft timing analysis in most cases lacks sufficient accuracy to identify the small normal magnetic field components expected to accompany such struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Tsurutani et al (1994) and Tsurutani and Ho (1999) have shown that DDs often occur at the edges of Alfvén waves and have argued that RDs are the phasesteepened edges of Alfvén waves, with the magnetic field rotations in the wave and the RD together forming a dual arc. Such arc-polarized cases occur in our data set and have been the focus of two earlier papers (Sonnerup et al, 2010;Haaland et al, 2012). They are clear cases of RDs by virtue of their finite normal magnetic fields.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Tsurutani et al (1994) and Tsurutani and Ho (1999) have shown that DDs often occur at the edges of Alfvén waves and have argued that RDs are the phasesteepened edges of Alfvén waves, with the magnetic field rotations in the wave and the RD together forming a dual arc. Such arc-polarized cases occur in our data set and have been the focus of two earlier papers (Sonnerup et al, 2010;Haaland et al, 2012). They are clear cases of RDs by virtue of their finite normal magnetic fields.…”
Section: Discussionmentioning
confidence: 56%
“…Knetter et al (2004) actually showed that the angle between the MVA and triangulation normals decrease with increasing eigenvalue ratio, reducing the angle to about 10 • if only cases with eigenvalue ratios > 10 were accepted. Moreover, a recent study has demonstrated that if MVA is applied carefully, and only large (> 20) eigenvalue ratios are accepted, small but significantly nonzero values of B n can be identified for a class of DDs referred to as arc polarized (Haaland et al, 2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…There is a clear correlation between Δv l and Δv A (except for discontinuities with |Δv l | insufficiently large to be defined), but instead of |Δv A | ∼ |Δv l | we observe |Δv A | ∼ 2|Δv l |. And, indeed, the observed discontinuities are characterized by B m peaks around the B l reversal shown in Figure 4c (see also Haaland et al, 2012;Sonnerup et al, 2010, and hodographs B m (B l ) for discontinuities from Figures 2 and 3 in Figures 5a and 5b). This difference can be due to missing ion component of the pressure anisotropy (which can be quite significant; see the solar wind statistics in Wilson et al, 2018) in equation (1), and thus more accurate measurements of the solar wind ion component are needed to estimate the relation between |Δv A | and |Δv l |.…”
Section: Discontinuity Structurementioning
confidence: 57%
“…The inverse correlation of Δn e and ΔT e can be explained by the absence of plasma pressure variations across discontinuities Δ(n e (T e + T i )) ∼ 0 (note that the electron and ion contributions to the plasma pressure are comparable; see (Wilson et al, 2018); we cannot estimate accurately the ion temperature for our data set, and thus Figure 4b only indicates on a relation Δ(n e (T e + T i )) ∼ 0 but cannot prove it). And, indeed, the observed discontinuities are characterized by B m peaks around the B l reversal shown in Figure 4c (see also Haaland et al, 2012;Sonnerup et al, 2010, and hodographs B m (B l ) for discontinuities from Figures 2 and 3 in Figures 5a and 5b). Therefore, the pressure balance across discontinuities 10.1029/2018GL079906 is approximately described as B 2 l + B 2 m ≈ const, whereas main currents in such magnetic field configuration are field aligned (see models proposed by Artemyev, 2011;Harrison & Neukirch, 2009).…”
Section: Figures 2e and 3e Show The Electron Anisotropy Plotted As A mentioning
confidence: 60%
“…In contrast to CSs with large β , small‐ β CSs are supported by field‐aligned currents [e.g., Harrison and Neukirch , ]. Such CSs are observed in solar wind [e.g., Haaland et al , , and references therein] and also believed to be generated during solar flares (e.g., see discussions in Allanson et al [] and Wilson et al []). Accurate investigation of such CS requires good temporal resolution of plasma measurements (unavailable for solar wind and solar corona), which can be provided for MAVEN observations (see example in Figure ).…”
Section: Three Groups Of Cssmentioning
confidence: 99%